2023
DOI: 10.1111/cote.12672
|View full text |Cite
|
Sign up to set email alerts
|

The roles of polymer relaxation phenomena, aqueous dye solubility and the physical properties of water in the mechanism of adsorption of a disperse dye on poly(ethylene terephthalate) fibres: Part 4 further aspects related to polymer relaxation phenomena

Abstract: To further investigate the contribution of polymer relaxation times to the mechanism of disperse dye adsorption on poly(ethylene terephthalate) fibres, the temperature‐dependent uptake of Teratop Yellow HL‐G 150% on both cotton and polyamide 66 fabrics at temperatures between 30 and 130°C was compared with that on poly(ethylene terephthalate) fabric. Although uptake of the commercial grade dye on polyester fabric is governed by the thermally regulated, broad glass transition of the water‐saturated poly(ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…Although very similar dye uptake versus temperature profiles were secured for all three types of fabric when dyeing had been undertaken at temperatures above the endset temperature of the glass transition of the respective water‐plasticised fabric, namely, ≦ 30°C in the case of both cotton and PA 66 and 110°C for PET, the dyeing temperature profile obtained for PET fabric differed considerably to that of its cellulosic and nylon fabric counterparts in the case of dyeing temperatures that were below the endset temperature of the PET glass transition (ie < 110°C) 1 …”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Although very similar dye uptake versus temperature profiles were secured for all three types of fabric when dyeing had been undertaken at temperatures above the endset temperature of the glass transition of the respective water‐plasticised fabric, namely, ≦ 30°C in the case of both cotton and PA 66 and 110°C for PET, the dyeing temperature profile obtained for PET fabric differed considerably to that of its cellulosic and nylon fabric counterparts in the case of dyeing temperatures that were below the endset temperature of the PET glass transition (ie < 110°C) 1 …”
Section: Introductionmentioning
confidence: 90%
“…The previous part of the study 1 showed that when the commercial grade disperse dye Teratop Yellow HL‐G was applied to cotton, polyamide 66 (PA 66) and poly(ethylene terephthalate) (PET) fabrics, over the broad range of dyeing temperatures between 30 and 130°C, the temperature dependent uptake of the dye on each type of substrate concurred with the fundamental premise of the free volume model of dye diffusion, insofar as, dye uptake was observed for all dyeing temperatures that were above the onset temperature of the glass transition of the respective water‐plasticised cellulosic, nylon 66 or polyester substrate, namely cotton = 0°C, PA 66 = −10°C and PET = ~65°C, this particular thermal transition parameter being referred to as the fibre's wet T g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations